User Interface Design of Interactive Video Based on Balinese Local Cultural Values Data in the Menek Daha Ceremony to Support Character Education - Sudiarta, I Wayan; Divayana, Dewa Gede Hendra; Tegeh, I Made; Sudatha, I Gde Wawan (Journal of Applied Data Sciences, 2025)
The presence of interactive videos based on Balinese local cultural values data in the Menek Daha ceremony is very important to socialize knowledge about character education in learning process at the senior high school level in the independent learning policy. One of the benchmarks for the ease of developing an interactive video is the readiness of its user interface design. The reality found in the field is that there are still many interactive video creators who do not care about user interface design. The challenges are especially if the stages of making the user interface design are based on data/information related to Balinese local culture. Therefore, the purpose of this study was to show the user interface design of an interactive video based on Balinese local cultural values data (Menek Daha ceremony) in supporting character education in the independent learning policy. This was a research and development using the Borg and Gall development model which focuses on the design stages, initial testing of the design, and revisions. The subjects involved in testing the user interface design were 84 respondents. The test tool was a questionnaire consisting of 15 questions related to the user interface design of an interactive video based on Menek Daha ceremony data. Analysis of trial data was carried out by comparing the percentage of user interface design quality with quality standards referring to the five scale categorizations. The results of this research show that the quality of user interface design of interactive videos based on Menek Daha ceremony data is in the good quality category by a quality percentage of 81.83%. This research novelty is the emergence of an interactive video user interface design integrated with Balinese local cultural values data in the Menek Daha ceremony as a learning technology innovation in supporting character education in independent learning policy.